Performance Analysis of STBC 4x4 MIMO using Ray Tracing Channel Modelling in WLAN Technology - Hasbi Nur Prasetyo Wisudawan; Suhartono Tjondronegoro (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
IEEE 802.11n technology comes with many advantages such as high data rate and reliability. In 2,4 GHz and 20 MHz bandwidth, it gives data rate up to 300 Mbps. In order to improve reliability without complexity, it uses STBC (Space Time Block Coding) using Alamouti algorithm. This algorithm can be implemented with many STBC scheme, i.e., 2x1, 2x2, 3x1, 3x2, 3x3, 4x1, 4x2, 4x3 and 4x4 using BPSK, QPSK, 16-QAM and 64-QAM modulation. Impulse respons of (Laboratorium Telekomunikasi Radio dan Gelombang Mikro) LTRGM indoor channel can be modeled by using ray tracing method. This simulation also investigates the effect of MIMO channel corelation caused by channel fading and physical antenna factor. The results, LTRGM indoor channel give delay spread and rms delay of 71.94 ns and 1.5 ns respectively. The ergodic channel capacity declines steadily as the channel correlation becomes worse. This problem also cause a decrease in SNR performance to achieve SER of 10-3 with various modulation. However, this does not have significant influence on WLAN system that uses STBC with four both transmit and receive antenna